Identity discover who you are and live a life of purpose - Jakes, T.D. (Shippensburg Destiny Image, 2015)
You have been uniquely created by God? to fulfill your divine purpose! In a day where so many people are frustrated, looking in different places to discover their life purpose and true meaning, you have the answer. Look no further than who you are!